Review of Grassroots Resources Region I - DENNIS M. DYER (Tufts Archival Research Center, 2007)
Memo from Dennis Dyer to George Minshew regarding the influence of grassroots activity in the actions of the Tobacco Institute in New England. Addresses the issue of what is a grassroots group and what can be expected of them. Discusses this issue in each state. Asks that one groups success be examined with regard to their size and influence since grassroots groups may not have as large an impact on tobacco affairs but are still incredibly important.